Radical-Mediated Difunctionalization of Styrenes - Bao, Xiazhen; Li, Jun; Jiang, Wei; Huo, Congde (Synthesis, 2019)
Styrene, an extremely important compound in the chemical industry, is mainly produced by the dehydrogenation or oxidative dehydrogenation of ethylbenzene. Transformation of this raw organic material to more useful fine organic chemicals is a very significant topic. Recently, the radical difunctionalization of styrene has become a powerful and efficient tool for organic synthesis. This strategy can introduce two substituents into a styrene molecule in one step via addition to the C=C bond, enhancing the molecular complexity in a single operation with good selectivity and wide functional group compatibility.1 Introduction2 C-Centered Radicals3 CF3 and Other Polyfluoroalkyl Radicals4 N-Centered Radicals5 P-Centered Radicals6 O-Centered Radicals7 S-Centered Radicals8 Other-Atom-Centered Radicals9 Conclusion and Perspective
Keywords: radical; difunctionalization; styrene; alkene; multicomponent reaction; step economy